Analisis Faktor-faktor Yang mempengaruhi Struktur Modal Perusahaan-perusahaan Pada Sektor Industri Properti Yang Terdaftar di Bursa Efek Indonesia Periode 2008-2010 - , Dwi Ananto, Boyke Rudy Purnomo, SE., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Failures in the management of cash flow often occurs in real estate and properties industry in Indonesia. The nature of property environments industry has a fairly high dynamics due to the stages of the production process is always surrounded by conditions that are always critical. High reliance on the use of mix of equity and debt in a variety of companies in this sector leading to frequent shocks due to macroeconomic conditions such as currency exchange rates and inflation. On the monetary crisis in 1998, the sector most affected are real estate and property industry, at that time about 60% of property company (1500 developers) have experienced bankruptcy and bad credit due to changes in currency value (monetary) and Bank Indonesia interest rates sharply(Perfindo, 1999). The companies in the industrial sector and the real estate property that has a dynamic business cycle as revealed in the study Sukardi (2009) is very dependent on the amount of debt mix (degree of leverage) owned. It is the goal of the studies so that the results can be information to define some policies of mix of debt that can enhance shareholder value in different conditions encountered. This study was to determine the factors operating leverage, asset structure, growth, return on assets (ROA), price earnings ratio (PER), and liquidity as the independent variable affects the structure of the debt ratio (DER) as the dependent variable. Multiple regression coefficients performed to determine the amount of each factor so that it can be tested with the F test as a simultaneous test and t test was performed to test the effect partially dependent variable on the independent variable. The results of this study are the factors simultaneously operating leverage, asset structure, growth, return on assets (ROA), price earnings ratio (PER), and liquidity has a significant effect on the amount of capital structure (DER) while only partial liquidity factor which shows a significant negative effect on capital structure, this means that there is a tendency to enterprises in the industrial sector of real estate and properties to avoid debt if the level of liquidity in the company scored well.